THE INFLUENCE OF MACROENVIRONMENTAL FACTORS ON THE FORMATION OF THE MARKETING COMPLEX OF A FRUIT AND BERRY SELLING ENTERPRISES - BINCHEVA, Polina (Herald of Khmelnytskyi National University. Economic sciences, 2022)
Orientation of agribusiness to the modern organization of marketing activity requires innovation and adaptation of work with consumers to market conditions. At the same time, the development of digital technologies and personalized marketing dictate the need to apply a clear strategy for the introduction of a marketing complex. Interactive communication with the consumer, the development of social networks and their impact on doing business on the Internet determine new approaches to planning the marketing complex at the enterprise. Today, marketing is moving from market competition to a market where demands and needs are created by the consumer himself. While processing enterprises quickly reoriented themselves to the requirements of digital marketing, most agricultural enterprises operating in the B2B system do not have such experience. This issue is especially relevant when carrying out export operations, when the company does not have experience in researching consumers in the digital space, analyzing export opportunities, and models for entering the foreign market. The above reasons create an extremely uncompetitive position for domestic enterprises in the production and sale of fruits and berries.The purpose of the study is to determine the main aspects of the formation of the marketing complex on the example of a typical agricultural enterprise on the fruit and berry market, taking into account macro-environmental factors.In order to ensure the perspective development of the fruit and berry market of Ukraine and to maintain a leading position on the regional, all-Ukrainian and world markets, it is necessary to: increase the investment attractiveness of domestic enterprises on the foreign market; increasing the level of productivity of products due to the introduction of the latest varieties and crops; compliance with the requirements of European countries for technological standards for the production of food products; increase in state funding of scientific and technical developments; organization of logistical ways of supplying products to the markets of the country and the world; increasing the attractiveness of environmentally friendly products due to the promotion of a healthy lifestyle. In our opinion, all these measures will contribute to increasing the competitiveness of fruit and berry producers both on the domestic and world markets.
Keywords: marketing complex; microenvironment; economic factors; demographic factors; technological factors; natural factors